PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA SOSIOLOGI PADA KELAS XI IPS SMA SEMEN PADANG - Gusweri, Intan; Melia, Yenni; Yasin, Faishal (Pendidikan Sosiologi, 2014)
The low due to lack of student learning outcomes varied learning model used by the teacher in the learning process . Though many instructional model used , one model of Problem Based Learning therefore, this study was conducted in order to see the significance of the model of Problem Based Learning to the student learning outcomes in subjects high school sociology class XI IPS SMA Semen Padang . This type of research is experimental research . The population in this study were all high school students of class XI IPS Semen Padang, which consists of 3 classes . The sampling technique is done randomly , class XI IPS3 as experimental class and class XI IPS2 as the control class . The instrument used in this study is the final test . Form of the test used is a form of multiple choice test reliability is r_11 = 0.84 . Based on the analysis of data obtained final test average student learning outcomes experimental class was 80.75 higher compared to the control class is 64.69 . Data analysis obtained t_hitung = 4.355 greater than t_tabel = 1.67 . Thus , it can be concluded that the model of Problem Based Learning as a model of learning that provides a positive impact on student learning outcomes .